Benthic cyanobacteria composition and microcystin concentration in the sediment of the Tri An Reservoir - Thanh Luu, Pham; Hoang Yen, Tran Thi; Ha, Bui Manh; Cam Loan, Tu Thi; Thi Thanh Thuy, Hoang; Thanh Son, Dao; Tu, Nguyen Van; Thai, Tran Thanh; Quang, Ngo Xuan (Vietnam Journal of Biotechnology, 2022)
The occurrence of cyanobacterial blooms (CYBs) associated with cyanotoxins has been reported worldwide. While planktonic cyanobacteria and the contamination of microcystin (MC) in the water column have been the subject of many investigations, little attention is paid to the benthic cyanobacterial communities and MC concentration in the benthic environment. This study aimed to investigate the benthic cyanobacterial composition and MC concentration accumulated in sediment from the Tri An Reservoir (TAR), Dong Nai province. Benthic cyanobacterial communities and sediment were collected at five sites in dry and rainy seasons. The benthic cyanobacterial communities were morphological observation and identification. Different nitrogen, phosphorus species, and chlorophyll-a (Chl-a) in sediment were analyzed. MCs concentration in sediment was quantified by High-Performance Liquid Chromatography (HPLC). Results indicated that the sediment from the TAR was contaminated with nitrogen. A total of 19 species belonging to 12 genera, 3 orders of cyanobacteria were identified. In which, Anabaena, Oscillatoria, and Microcystis were the three most commonly found in the samples. Surface sediment samples contained high densities of colonial Microcystis. The Chl-a concentration in sediment in dry and rainy seasons ranged from 1.96–3.45 and 0.71–3.15 µg/g fresh weight (FW), respectively. MC was detected in sediment at all sites in both dry and rainy seasons with a concentration up to 191.4±14.2 ng/g FW. The outcome of this study provides basic knowledge on MC and potential MC-producing cyanobacteria in a drinking water supply. Further investigation on the toxic producing ability of the benthic cyanobacteria species from the Tri An Reservoir is required.